Identification of a novel protein truncating mutation p.Asp98* in XPC associated with xeroderma pigmentosum in a consanguineous Pakistani family. Issue 2 (10th January 2020) - Ali, Muhammad Z.; Blatterer, Jasmin; Khan, Muzammil A.; Schaflinger, Erich; Petek, Erwin; Ahmad, Safeer; Khan, Ejazullah; Windpassinger, Christian
Abstract: Background: Xeroderma pigmentosum (XP) is a rare genetic disorder, which is characterized by hyper‐sensitivity to solar ultraviolet (UV) radiation. Clinical consequences of sun exposure are skin lesions and an increased risk of developing skin cancer. Genetic studies have identified eight genes associated with xeroderma pigmentosum. The proteins encoded by these genes are mainly involved in DNA repair mechanisms. Methods: Molecular genetic characterization of patients with xeroderma pigmentosum involved positional cloning methods such as homozygosity mapping and subsequent candidate gene analysis. Mutation screening was performed through Sanger DNA sequencing. Results and Discussion: In this case study, we report a novel protein truncating mutation in XPC associated with autosomal recessive xeroderma pigmentosum in a consanguineous Pakistani family. Genetic mapping revealed a novel single base insertion of a thymine nucleotide NM_004628.4: c.291dupT (c.291_292insT) in the second exon of XPC . The identified mutation leads to a premature stop codon (TGA) at amino acid position 98 (p.Asp98*) and thus presumably results in a truncated protein. The Xeroderma pigmentosum, complementation group C ( XPC) is located on 3p25.1 and encodes a protein involved in nucleotide excision repair. The identified mutation presumably truncates all functional domains of the XPC protein, which likely results in the loss of protein function. Conclusion: The study expands the knowledge of the mutational spectrum of XPC and is valuable for genetic counseling of affected individuals and their families. Abstract : In this study, we report a novel protein truncating mutation (p.Asp98*) in XPC of xeroderma pigmentosum patient. The identified mutation presumably truncates all functional domains of the XPC protein, which likely results in the loss of protein function. The study expands the knowledge of the mutational spectrum of XPC and would be valuable for genetic counseling of affected individuals and their families.